The role of topography in the micro-fabrication of an intervertebral disc - Lim, Chee Seong (2015)
Cell behavior can be manipulated by the topography of the culture substrate. In this study, we examined the cell alignment of multipotent mesenchymal stem cell (MSC) on a grill topographical pattern of porous poly(L-lactide/Caprolactone) (PLC) substrate. Electron microscopy showed that MSC integrated and interacted well with PLC substrate and promoted directional growth through the grill guidance. Subsequently, we embossed this finding on the microfabrication of intervertebral disc (IVD) construct that posed a multilayer concentric-orientated and alternate cross-aligned organization to resemble the fibrocartilagenous Annulus Fibrosus (AF). Samples were cultured under growth medium for 2 weeks and rolled up for another 4 weeks chondrogenic medium culture. Histology revealed the microarchitecture of PLC scaffold and distribution of fibrocartilagenous tissue. Biochemical analysis showed that the expressions of chondrogenic marker genes (COL1, COL2 and Aggrecan) were significant and expression of COL2 was the most significant. The mean tensile modulus of control and grill-topographic PLC scaffolds were 2.18 MPa and 3.3 MPa respectively. This studies document the feasibility of creating biphasic tissue-engineered intervertebral disc construct in mimicking microarchitecture of native AF.